Adapting and Validating the Academic Self-Efficacy Scale for Advanced-Level Students in Sri Lanka - Piratheeban, K.; Bandara, L.M.K. (Faculty of Education, University of Colombo, 2025)
Academic self-efficacy (ASE) plays a vital role in shaping students’ motivation, persistence, and academic success. Despite its theoretical importance and frequent use in international settings, there is a lack of a validated scale for measuring ASE among advanced-level students in the Sri Lankan context. This study introduces and validates the Academic Self-Efficacy Scale (SL-ASESAL), tailored for advanced-level students in Sri Lanka. The scale was adapted from Dullas (2018) and comprises three dimensions: Perceived Control, Competence, and Persistence, with Selfregulated Learning excluded, as it is considered a distinct construct within the broader research framework. The validation process employed a three-phase approach, consisting of a two-round Delphi and a pilot study. In the first round, responses from 14 experts were analyzed, resulting in the exclusion of items that fell below the 80% consensus threshold. This process led to 16 items advancing to the second round. In the second round, eight experts evaluated these items for relevance and clarity. Using the Item-Level Content Validity Index (I-CVI) and Scale-Level Content Validity Index, all items attained the maximum I-CVI value of 1.00, indicating excellent content validity. Subsequently, a pilot study was conducted with 64 advanced-level students to assess reliability and construct validity. An overall Cronbach’s alpha of .841 and dimensionspecific alpha values above .70 confirmed high internal consistency. Item-total correlation values further supported construct validity, with eleven items demonstrating strong correlations (≥ .5), and five items rated as acceptable. One item, with a slightly lower correlation, was retained in a rephrased form based on expert judgment. These findings confirm that the adapted SL-ASES-AL scale is both valid and reliable for assessing ASE within the Sri Lankan context. It offers a contextually relevant tool to enhance educational assessment and student well-being.
Keywords: Academic self-efficacy; Scale adaptation; Content validity; Construct validity; Delphi method